(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Online social network has developed significantly in recent years. Most of current research has utilized the property of online social network to spread information and ideas. Motivated by the applications of dominating set in social networks (such as e-learning), a variation of the dominating set called positive influence dominating set (PIDS) has been studied in the literature. The existing research for PIDS problem do not take into consideration the attributes, directions and degrees of personal influence. However, these factors are very important for selecting a better PIDS. For example, in a real-life e-learning community, the attributes and the degrees of their influence between a tutor and a student are different; the relationship between two e-learning users is asymmetrical. Hence, comprehensive, deep investigation of user’s properties become an emerging and urgent issue. The focus of this study is on the degree and direction between e-learners’ influence. A novel dominating set model called weighted positive influence dominating set (WPIDS), and two selection algorithms for the WPIDS problem have been proposed. Experiments using synthetic data sets demonstrate that the proposed model and algorithms are more reasonable and effective than those of the positive influence dominating set (PIDS) without considering the key factors of weight, direction and so on.